METHODOLOGICAL CHARACTERISTICS IN MODERN STORYTELLING (AS AN EXAMPLE OF “THE WIND CANNOT BE CAUGHT” BY NAZAR ESHONKUL) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article examines stylistic updates and artistic skills in modern Uzbek prose using the example of Nazar Eshonkul’s story “The Wind Cannot Be Caught”. The author’s methods of using symbols and metaphors, his unique approach to describing the psyche of the characters, and the philosophical layers of the work are analyzed.
Keywords: modern storytelling, loneliness and suffering, perseverance, pride.